The Iban Community's Perception: The Taste, Ingredients, and Cooking Methods of Ibanese Traditional Chicken Dish - Emmanuel Aaron Alvin Uping Bernadine,; Nurul Hidayah Liew Abdullah, (Online Journal for TVET Practitioners, 2024)
Traditional food is part of the culture, identity and heritage for every nation or race found in a country around the world. In Malaysia, its diverse community has contributed various productions in terms of heritage cuisine that shows identity such as cooking methods and food presentation. However, Manuk Pansuh is increasingly forgotten and the Iban community now lacks knowledge in the science of preparing Manuk Pansuh. Manuk Pansuh which is usually found during the Gawai Dayak festival season only. However, Manuk Pansuh is now available in restaurants but cannot meet the demand of the public. Therefore, this study aims to identify the perception of the Iban community towards Manuk Pansuh. The design of this study is a survey study using a quantitative approach. Questionnaire forms are used as a tool to collect information and also data from respondents accurately and authentically. The sample of this study consisted of 50 respondents from the Iban community. The findings of this study were analyzed using SPSS version 26 through frequency, percentage, mean and standard deviation. The result of the study show that the Iban community's perception of the ingredients and cooking methods of Manuk Pansuh is at a high level. However, the Iban community's perception of the taste of Manuk Pansuh is at moderate level. In conclusion, the Iban community needs to improve and preserve the ethnic traditional food. Therefore, each individual should play a role so that this unique traditional food does not become extinct in the era of modernization.